Seasonal variations in daily mortality associated with exposure to particulates, in Campo Grande, Brazil - Raquel Soares Casaes Nunes; José Francisco de Oliveira-Júnior; Marcel Carvalho Abreu; Flavio Aristone; Widinei Alves Fernandes; Amaury de Souza; Cícero Manoel dos Santos; Débora Martins de Souza (Universidade do Estado de Mato Grosso, 2022)
Obcjetive: to investigate short-term effects of air pollution, climate variability on respiratory morbidity and mortality from 2005 to 2020. Method: the study was carried out in the city of Campo Grande, Mato Grosso do Sul, Brazil. Daily counts of hospital admissions from 2005 to 2020 were analyzed in relation to daily variations in atmospheric pollutants (NO2, O3) from the Aurea satellite column, OMI sensor. Poisson regression in generalized additive models was used for analysis. The models were adjusted for the effects of temporal trend, seasonality, meteorological factors and autocorrelation. Results: there was, in the period, an increasing trend in mortality rates and hospital admissions, with an increase in the proportion of deaths from respiratory diseases in relation to other causes. Conclusion: respiratory diseases are worrying causes of hospitalization and death in the population. The results found are consistent with studies that point to an association between short-term variations in air pollutants and the increase in morbidity and mortality in large urban centers.